The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1590/s0034-89101995000400001
|View full text |Cite
|
Sign up to set email alerts
|

Ação da inoculação de hemolinfa no mecanismo de defesa de Biomphalaria tenagophila (Orbigny, 1835)

Abstract: Estudou-se a resistência à infecção pelo S. mansoni em moluscos B. tenagophila inoculados com vários tipos de hemolinfa provenientes de moluscos infectados por S. mansoni da linhagem SJ ou por outros trematódeos avaliando-se, nestas circunstâncias, o comportamento dos amebócitos. Concluiu-se que dois tipos de mecanismos teriam agido provocando resistência à infecção pelo S. mansoni: celular e humoral. A reação do tipo celular ocorreu quando os moluscos eram inoculados com hemolinfa de moluscos infectados por S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Pan (1996) suggested that, under appropriate conditions, B. glabrata hyalinocytes can become granulocytes. Reis et al (1995) noted a direct correlation between the resistance to infection by Schistosoma mansoni and sporocyst death; this observation suggested that hemocytes were an important factor in fighting infections. Kassim and Richards (1979), Sullivan and Richards (1981), and Guaraldo et al (1981) confirmed that sporocyst development in susceptible mollusks was slow, whereas in non-susceptible mollusks the sporocysts were surrounded by defense cells and were quickly killed.…”
mentioning
confidence: 95%
“…Pan (1996) suggested that, under appropriate conditions, B. glabrata hyalinocytes can become granulocytes. Reis et al (1995) noted a direct correlation between the resistance to infection by Schistosoma mansoni and sporocyst death; this observation suggested that hemocytes were an important factor in fighting infections. Kassim and Richards (1979), Sullivan and Richards (1981), and Guaraldo et al (1981) confirmed that sporocyst development in susceptible mollusks was slow, whereas in non-susceptible mollusks the sporocysts were surrounded by defense cells and were quickly killed.…”
mentioning
confidence: 95%
“…However, the data collected thus far have not supported this hypothesis. In addition, other researchers have failed to demonstrate a consistent finding between the tissue response and its effect on cells from the haemolymph (Reis et al 1995, Borges 2005). In addition, as first noted by Jeong et al (1983), our ultrastructural findings demonstrated that the APO is a complex structure that is composed of juxtaposed cells with epithelial characteristics, such as microvilli, on its free surface.…”
Section: Discussionmentioning
confidence: 99%